Localisation and stimulation of the parietal eye field*. Issue 2 (7th June 2022) - Phamnguyen, Thienan John; Wijayath, Manori; Bleasel, Andrew; Rahman, Zebunnessa; Bartley, Melissa; Dexter, Mark; Wong, Chong
Abstract: Localisation of the human parietal eye fields (PEF) has not been as well studied as the human frontal eye fields (FEF). Stimulation studies in rhesus monkeys have suggested the localisation of the PEF to be within the intraparietal sulcus. Functional MRI studies have demonstrated this region to be highly active and potentially connected in saccadic and gaze shifting tasks. Here, we present a case of a patient with left versive seizures evaluated with SEEG, in whom electrical stimulation within the right intraparietal sulcus resulted in horizontal and downward conjugate eye movements contralateral to stimulation. We illustrate clinical differences between the FEF and PEF on cortical stimulation. In addition to the frontal eye field, it is important to recognise other cortical regions involved in eye movement which can cause conjugate contralateral eye movement.